Shed and Unshed Blood in Dostoevsky’s Novel “Crime and Punishment” - Polina E. Nikolaeva (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2018)
This work is an attempt to consider the motive of blood in F.M. Dostoyevsky's novel “Crime and Punishment”. Blood is not simply a repeating word in the novel: in my opinion, the question of shed blood is a main one. The essence of this work is the observation of how heroes answer this question. It seems to me that this proceeding can help us to get closer to the understanding of the main meanings of the novel “Crime and Punishment”.